State of the Art on Retrofitting of Fatigue Damaged Concrete Structures - Yas, Shiemaa Taha; Al-Hadithy, Laith Khalid (Al-Nahrain Journal for Engineering Sciences, 2024)
This article provides a general up to date review of the investigation on performances and resistances of plain and fiber containing concrete structures under periodical loadings of long endurance up to fatigue failure. Structures are almost, under the frequent influences of repeated loadings such as vibrations of rotary machines, sea /river waves, wind, earthquakes and moving vehicles. Long term application of cyclic loading leads to continually slow rate degradation of the structure rigidity leading to fatigue damage. In spite of the dominant usage of concrete, worldwide, as a building material, its fatigue behavior is not straight forward. In addition, this lack of comparison is confronted for fiber fortified concrete. The article also presently a survey of the available techniques for monitoring and measurement of fatigue impressions in concrete structures founded both their impact within the treatise domain and the non-destructive inspection. Those technical means are classified into, at least, two designations, specifically, the monitoring of fatigue induced cracking and the detection of fatigue charged damage. Those techniques parameters, evaluate the changes in the mechanical and physical materials properties during the fatigue endurance, are distantly reviewed in concern of the mechanism creating the change, shortcomings, constraints, etc. The merits, dependency, feasibility, disadvantages and limitations of each technique are assessed and compared to make an index to select the appropriated e technique for fatigues fracture or failure inspection of the type fibered or not of structural concrete